Mathematics an applied approach : student solutions manual - Mizrahi, Abe (John Wiley & Sons, 1996)
Comprehensive and clearly written, Mathematics offers a variety of topics applicable to the business, life sciences and social sciences fields, such as Statistics, Finance and Optimization.